Analysis of Grammatical Errors in EFL Students' Recount Texts - Frihatmawati, Rizky; Dhini, Ulfa Rahma; Rentiana, Leny Hikmah; Yuskar, Bobby Octavia (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
Writing in a foreign language is one of the most challenging skills. Consequently, grammar errors continue to be a significant challenge in writing for individuals learning English as a second language. Analyzing the errors made by EFL students is essential as they offer valuable insights into the second language acquisition process. This study aimed to identify the main kinds of grammatical issues and the key sources of grammatical errors in students' recount text. This research was conducted as a descriptive qualitative study. This study focused on the texts produced by first-semester students in the Information System Department during the General English Classroom. The data were identified and examined using the error theory proposed by Dulay et al. (1982) on surface approach taxonomy and the concept of the source of errors introduced by Brown (2007). The data revealed that the predominant type of grammatical error was misformation, with 35 errors or 37.33% of the total errors. The predominant source of grammatical errors was intralingual transfer, leading to 48 errors, which constituted 43.43% of the overall total.